Penentuan Kadar Total Fenol dan Uji Aktivitas Antioksidan Ekstrak Etanol Herba Seledri (Apium graveolens L.) dengan Metode DPPH - Wiranda Gultom; Razoki Razoki; Refi Ikhtiari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Celery (Apium graveolens L.) is a herbal plant that has long been used in traditional medicine. This plant contains various bioactive compounds such as flavonoids, tannins, and phenolic compounds that play important roles as natural antioxidants. The DPPH method is commonly used to evaluate the ability of antioxidant compounds to scavenge stable DPPH free radicals, resulting in a color change from purple to yellow as the radical concentration decreases. Objective: This study aimed to determine the total phenolic content and antioxidant activity of ethanol extract of celery (Apium graveolens L.) using the DPPH method. Methods: This study employed a laboratory experimental design with a quantitative descriptive approach. The research was conducted from May to December 2025 at the UNPRI Laboratory and USU Laboratory. Results: The quality parameter evaluation of ethanol extract of celery (Apium graveolens L.) showed a moisture content of 5.9%. The total ash content was 15.6%, while the acid-insoluble ash content was 2.19%. The water-soluble extractive value and ethanol-soluble extractive value were 17.49% and 7.37%, respectively. The average total phenolic content obtained was 102.104 ± 0.3032 mgGAE/g extract, indicating that the ethanol extract of celery contains relatively high phenolic compounds. The linear regression equation obtained was y = 0.0083x + 0.0052 with a coefficient of determination (R²) of 0.9894. The R² value close to 1 indicates a very strong linear relationship between gallic acid concentration and absorbance, suggesting that the calibration curve met the validity requirements for total phenolic determination. Conclusion: Based on the results of this study, the ethanol extract of celery (Apium graveolens L.) exhibited an IC₅₀ value of 21.023 µg/mL, which is categorized as a very strong antioxidant. Although the IC₅₀ value was higher than that of quercetin, the antioxidant activity of the extract was still considered very good for a crude plant extract.